Next of kin's experiences of involvement during involuntary hospitalisation and coercion. Issue 1 (December 2016) - Førde, Reidun; Norvoll, Reidun; Hem, Marit; Pedersen, Reidar
Abstract Background Norway has extensive and detailed legal requirements and guidelines concerning involvement of next of kin (NOK) during involuntary hospital treatment of seriously mentally ill patients. However, we have little knowledge about what happens in practice. This study explores NOK's views and experiences of involvement during involuntary hospitalisation in Norway. Methods We performed qualitative interviews-focus groups and individual-with 36 adult NOK to adults and adolescents who had been involuntarily admitted once or several times. The semi-structured interview guide included questions on experiences with and views on involvement during serious mental illness and coercion. Results Most of the NOK were heavily involved in the patient's life and illness. Their conceptions of involvement during mental illness and coercion, included many important aspects adding to the traditional focus on substitute decision-making. The overall impression was, with a few exceptions, that the NOK had experienced lack of involvement or had negative experiences as NOK in their encounters with the health services. Not being seen and acknowledged as important caregivers and co sufferers were experienced as offensive and could add to their feelings of guilt. Lack of involvement had as a consequence that vital patient information which the NOK possessed was not shared with the patient's therapists. Conclusions Despite public initiatives to improve the involvement of NOK, the NOK in our study felt neglected, unappreciated and dismissed. The paper discusses possible reasons for the gap between public policies and practice which deserve more attention: 1. A strong and not always correct focus on legal matters. 2. Little emphasis on the role of NOK in professional ethics. 3. The organisation of health services and resource constraints. 4. A conservative culture regarding the role of next of kin in mental health care. Acknowledging these reasons may be helpful to understand deficient involvement of the NOK in voluntary mental health services.